2007
DOI: 10.1248/bpb.30.1697
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent Gb3-/Gb2-Derivatives Conjugated with a Phosphatidyl Residue: A Novel Class of Shiga Toxin-Neutralizing Agent

Abstract: Shiga toxin (Stx)-1 and Stx-2 are involved in the pathogenesis of hemolytic uremic syndrome (HUS) and severe systemic complications following enterohemorrhagic Escherichia coli (EHEC) infection in humans. [1][2][3][4] Stxs have an AB 5 structure, in which a single catalytic A subunit is associated with five identical B subunits. The B pentamer is responsible for the toxin binding to eukaryotic cell-surface glycolipid receptors such as galabiosyl (Gb 2 )-ceramide and globotriaosyl (Gb 3 )-ceramide. The suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The authors hypothesized that excess amounts of Gb3 may reduce toxin delivery to susceptible tissues. And indeed, Neri et al (18) could demonstrate that monovalent Stx ligands of phosphatidylethanolamine dipalmitoyl-Gb3 (Gb3-PEDP) and galabiosyl (Gb2)-PEDP strongly neutralized the cytotoxicity of Stx in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…The authors hypothesized that excess amounts of Gb3 may reduce toxin delivery to susceptible tissues. And indeed, Neri et al (18) could demonstrate that monovalent Stx ligands of phosphatidylethanolamine dipalmitoyl-Gb3 (Gb3-PEDP) and galabiosyl (Gb2)-PEDP strongly neutralized the cytotoxicity of Stx in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…The cytotoxicity assay was performed as described previously [17], [18]. Briefly, 5×10 3 /well of HeLa 229 cells (kindly provided by Dr. T. Yoshida, Aichi Medical University, Aichi Prefecture, Japan) were cultured in Dulbecco's Modified Eagle's Medium (DMEM) (Nissui Pharmaceutical) supplemented with 10% heat-inactivated fetal bovine serum (ICN Biomedicals, Aurora, OH, USA), 100 U/ml penicillin G and 0.1 mg/ml streptomycin with 96-well flat bottomed culture plates (Costar; Corning Inc., Corning, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, it has been shown that the affinity of Stx-1 for the glycolipid receptor is higher than that of Stx-2 [22], [23]. Therefore, the Gb 2 - or Gb 3 -conjugated compounds that have been reported as drug candidates show a good neutralizing activity against Stx-1, but are less active against Stx-2, although we recently reported that Gb 2 /Gb 3 -conjugated to phosphatidyl residues is relatively effective at neutralizing Stx-2 [18]. Importantly, it has been speculated that the low affinity of Stx-2 for the receptor might be involved in the higher toxicity in vivo [22].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Synthetic Gb 3 -conjugated compounds have been actively investigated for this purpose. [4][5][6] In another approach, monoclonal antibodies against Stx have been shown to neutralize Stx. [7][8][9][10] Stx released from EHEC in the intestine enters the bloodstream to reach the target organs.…”
mentioning
confidence: 99%